The Determinants For Purchase Intention Of Hybrid Cars In Penang, Malaysia - Goh, Kai Ning (2014)
This study examines the purchasing of hybrid cars in Penang, Malaysia by understanding the factors which influence the consumers’ purchase intention. Hybrid cars refers to a car which uses two or more distinct power sources to move. A hybrid car is also known as hybrid-electric vehicles (HEV) which is using an internal combustion engine with an electric motor. The importance of adopting a hybrid car has been gaining public attention due to its environmental conservation property as well as its fuel efficiency. However, studies which relates to the public perception on government policy, environmentalism as well as perceived value and perceived risk of this new technology product in Malaysia is less explored.